Efficacy of low-dose hypobaric anesthetics in spinal anesthesia for cesarean delivery: systematic review and meta-analysis - Min Li; Guohao Xie; Lihua Chu; Yan Li (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective Many studies have compared the anesthetic effects of different doses of hypobaric local anesthetics (without glucose) in spinal anesthesia for cesarean sections. Therefore, a meta-analysis of these trials is warranted.Methods Systematic review and meta-analysis of eligible randomized controlled trials comparing the efficacy of low-dose spinal hypobaric anesthetics (Bupivacaine < 10 mg, levobupivacaine < 10 mg, ropivacaine < 15 mg) with conventional dose (Bupivacaine/Levobupivacaine ≥ 10 mg, ropivacaine ≥ 15 mg) in elective and subemergency Cesarean sections in data sources (PubMed, Embase, Web of Science, and Cochrane Central) from inception to February 2025.Results We obtained data from 1,280 patients from 17 published trials. Low-dose hypobaric local anesthetics reduce hypotension occurrence (risk ratio [RR], 0.56; 95% confidence interval [CI], 0.43 to 0.73; low evidence grade) but comprise anesthesia effect (analgesic-supplementation risk: RR 3.13, 95%CI 2.14 to 5.59, moderate evidence grade). In the subgroup analysis (based on whether opioid adjuvants mixed with local anesthetics were equal), there were no differences in anesthetic effects between low-dose local anesthetics mixed with opioid adjuvants and conventional-dose local anesthetics without opioid adjuvants between the two groups (analgesic-supplementation risk: RR 1.32, 95%CI 0.58 to 3.00, moderate evidence grade). Other secondary outcomes, including hypotensive side effects (nausea/vomiting and bradycardia), ephedrine consumption, and highest block plane, were observed less or lower in the low-dose group. No significant differences were found in trembling, pruritus, time to maximum block, or neonatal outcomes between the two groups.Conclusion Low-dose hypobaric local anesthetics in spinal anesthesia may reduce maternal side effects (hypotension, nausea/vomiting, and bradycardia) but comprise anesthetic efficacy (analgesic-supplementation risk). Furthermore, intrathecal opioid adjuvants improve anesthetic efficacy.Details of registration The protocol for this systematic review was registered on PROSPERO (CRD42024533150).